Semiotika Riffaterre Dalam Puisi “Qabla an Numdhi” Karya Faruq Juwaidah - Cyntia Dewi Putri Gemilang (‘A Jamiy : Jurnal Bahasa dan Sastra Arab, 2022)
This study describes Riffaterre’s semiotics in a poem antitled “Qabla an Numdhi” by Faruq Juwaidah. He is a modern Egyptian poem who is famous for his love poems. The theme of this poem is about the image of a person who feels that he will return to his lord. This poem is different from other Faruq Juwaidah poems. While other poems talk about love for her lover, this poem describes how she love the God. This study aims to reveal the results of heuristic reading and hermeneutic reading in the poem entitled “Qabla an Numdhi” by Faruq Juwaidah with Michael Riffaterre’s semiotic analysis. This is a library research using qualitative descriptive research methods. The results of this study are: (1) the results of reading the heuristic of this poem tell a person who feels that he will return to his God; (2) the results of hermeneutic reading in this poem is to tell someone who feels miserable, sad because he feels that his life is in vain; (3) the matrix of this poem is regret; (4) the model of this poem is someone who is very sorry because during his youth he spent just having fun; (5) the hypogram of yhis poem is related to the hadith of Hasan al-Bashri.